The Influence of Leadership and Motivation on Performance in High-Discipline Organizations: A Study of Brimob Personnel - Hartati, Hartati; Setiawan, Akbar; Alyyasa-Gan, Siti Sarah; Machmud, Mulyana (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the effects of leadership and work motivation on personnel performance in a paramilitary institution, specifically Batalyon B Pelopor Brimob Parepare, and hypothesizes that both variables significantly influence performance, with motivation as the dominant factor. Research Method: A quantitative correlational design was applied using a census sample of 39 personnel in Parepare, Indonesia. Data were collected through structured questionnaires and analyzed using multiple linear regression to test both partial and simultaneous effects of leadership and motivation on performance. Results and Discussion: The findings indicate that leadership and work motivation both have positive and significant effects on personnel performance, individually and jointly. Motivation has a stronger influence than leadership. The regression model explains 93.3% of the variance in performance, indicating strong explanatory power. These results confirm the critical role of motivational factors in high-risk, structured organizational settings. Implications: The study highlights the importance of integrating effective leadership practices with robust motivational strategies to enhance performance in paramilitary organizations. It contributes to extending leadership–motivation–performance frameworks into underexplored contexts and recommends future research with larger samples and comparative institutional settings.